2021
DOI: 10.1002/jemt.23757
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphological, space, and mineral relations of dermal denticles in angular angel shark (Squatina guggenheim)

Abstract: Shark skin is predominantly specialized for swimming and protection, with the dermal denticle being the main structure associated with these abilities. The dermal denticle is a mineral structure with a unique morphology for each species, which allows its use as a taxonomic tool. Few studies have investigated the microscopy aspects of skin and dermal denticles, considering the high diversity of sharks. Here, we investigated the three‐dimensional morphoquantitative aspects and mineral composition of dermal denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…We observed that the dermal denticles of the caudal crest of G. mincaronei have a larger area of contact with the tegument than denticles in other areas of the body. De Lima Viliod et al (2021) reported a similar arrangement in the dorsal denticles of the Hidden angel shark Squatina guggenheim (Marini, 1936), attributing it mainly to defense. However, further histological or ecological studies are needed to identify the role and function of C1 dermal denticles in the genus Galeus or, more specifically, in the deep‐water shark G. mincaronei .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We observed that the dermal denticles of the caudal crest of G. mincaronei have a larger area of contact with the tegument than denticles in other areas of the body. De Lima Viliod et al (2021) reported a similar arrangement in the dorsal denticles of the Hidden angel shark Squatina guggenheim (Marini, 1936), attributing it mainly to defense. However, further histological or ecological studies are needed to identify the role and function of C1 dermal denticles in the genus Galeus or, more specifically, in the deep‐water shark G. mincaronei .…”
Section: Discussionmentioning
confidence: 93%
“…Higher densities of dermal denticles were observed in the P, D, and C2 fins of G. mincaronei , with no difference between the sexes. W. Raschi and Tabit (1992) and De Lima Viliod et al (2021) suggested that higher dermal denticle densities potentially indicate hydrodynamic functions or protection against abrasion. Larger dermal denticles, such as those we observed at the C1 site in G. mincaronei , at lower densities may confer defense or resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to explore the relationship between the flow field around the shark and the adaptive growth of scales, the physical parameters of scales were measured. The morphology, riblet size, roughness, and composition of shark scales have been previously studied in fine detail ( Motta et al, 2012 ; Popp et al, 2020 ; de Lima Viliod et al, 2021 ). A sub-set of 45 skin samples of 2 cm × 2 cm were carefully dissected from the different parts of the shark using pre-made templates consisting of plastic substrates and pins ( Figure 3A ).…”
Section: Methodsmentioning
confidence: 99%